1990
DOI: 10.1111/j.1365-2125.1990.tb03691.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intrasubject variability of gastric emptying in healthy volunteers measured by scintigraphy and paracetamol absorption.

Abstract: 1. Inter‐ and intrasubject variability in the gastric emptying of semisolids and liquids was measured by scintigraphic emptying of radionuclide‐labelled semisolid and from paracetamol absorption in ten healthy volunteers of both sexes. 2. The intrasubject variability was not statistically significant for any of scintigraphic or paracetamol absorption parameters. 3. The intersubject variation was significant for all scintigraphic and paracetamol absorption parameters. 4. In women, the gastric emptying rate of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 14 publications
1
48
1
1
Order By: Relevance
“…Some investigators have found a significant correlation between the parameters for the rate of paracetamol absorption and scintigraphically measured gastric half-emptying time, the "gold standard" for GER measurement, 9,[12][13][14][15] but others have failed to find such correlation. 16,17 Based on the absence of "significant" correlation, the validity of the paracetamol method has been challenged. 7 It should be noted that authors who were against the paracetamol method studied only healthy volunteers in whom disorders in GER were not anticipated 16,17 and, consequently, the range of half-emptying time would be relatively narrow.…”
Section: Validity Of Paracetamol Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators have found a significant correlation between the parameters for the rate of paracetamol absorption and scintigraphically measured gastric half-emptying time, the "gold standard" for GER measurement, 9,[12][13][14][15] but others have failed to find such correlation. 16,17 Based on the absence of "significant" correlation, the validity of the paracetamol method has been challenged. 7 It should be noted that authors who were against the paracetamol method studied only healthy volunteers in whom disorders in GER were not anticipated 16,17 and, consequently, the range of half-emptying time would be relatively narrow.…”
Section: Validity Of Paracetamol Methodsmentioning
confidence: 99%
“…16,17 Based on the absence of "significant" correlation, the validity of the paracetamol method has been challenged. 7 It should be noted that authors who were against the paracetamol method studied only healthy volunteers in whom disorders in GER were not anticipated 16,17 and, consequently, the range of half-emptying time would be relatively narrow. A "significant" correlation is unlikely to be found between quantities within limited ranges.…”
Section: Validity Of Paracetamol Methodsmentioning
confidence: 99%
“…Stomach transit time, which represents gastric emptying time, is a key factor determining the initiation of the absorption phase. It had been reported that stomach transit time has considerable variability [52][53][54] . If comparing the observed and simulated oral profiles indicates there is hysteresis of the initial absorption phase between them, the stomach transit time is higher than the average normal value used in the PBPK model and is required to adjust until the simulated profile captures the observed profile shape well [50] and has a lower value of the mean absolute error (MAE) and root mean square error (RMSE).…”
Section: Wb-pbpk Modeling Strategymentioning
confidence: 99%
“…However, individual model parameters' identification may be jeopardized by the presence of large intra-patient variability. This variability within an individual arises, among other causes, from the different physiological processes involved such as subcutaneous insulin absorption, circadian rhythms of insulin sensitivity, action of counter-regulatory hormones, meal digestion and absorption (which depend on meal composition and even previous meals ingested) [4], [5]. Patient variability can thus be a limiting factor to the performance of any insulin therapy.…”
Section: Introductionmentioning
confidence: 99%